HEALTH INSURANCE LITERACY, HEALTH STATUS, AND CONCERNS ABOUT AFFORDABILITY OF HEALTH INSURANCE NEAR RETIREMENT. (8th November 2019) - Scherer, Aaron M; Solway, Erica; Malani, Preeti; Luster, Jamie; Kullgren, Jeffrey; Kirch, Matthias A; Singer, Dianne; Tipirneni, Renuka
Abstract: Results from the NPHA highlight the link between health insurance affordability concerns and delaying/forgoing health care near retirement. We sought to determine factors associated with health insurance affordability concerns for US adults age 50-64. We regressed little/no confidence in health insurance affordability in retirement/within the next year on health insurance literacy, age, gender, race/ethnicity, income, employment, education, and health status. Factors associated with greater health insurance affordability concerns included lower health insurance literacy—measured via confidence knowing health insurance terms (aOR=1.78, p=0.035), identifying covered services (aOR=1.81, p=0.038), and finding out service costs (aOR=2.69, p<0.001)—female gender (aOR=1.73, p=0.001), and fair/poor health (aOR=1.88, p=0.020). Factors associated with fewer health insurance affordability concerns included African-American race (aOR=0.55, p=0.038) and higher income (aOR=0.34, p<0.001). These results suggest that it may be possible to reduce health insurance affordability concerns and delayed/forgone care by improving adults' confidence in understanding and using health insurance.